The Influence Of Sports Extracurricular Activities On Students' Social Skills - Agitated Jesilia Sembiring; Heka Maya Sari Br Sembiring; Reza Mahyuddin (Journal Physical Health Recreation (JPHR), 2025)
This study aims to determine the influence of sports extracurricular activities on the social skills of junior high school students. The method used is quantitative with a quasi-experimental design approach of the nonequivalent control group design type. The sample totaled 60 students, consisting of 30 students who participated in sports extracurriculars as an experimental group and 30 students who did not participate as a control group. The research instrument is in the form of a social skills questionnaire that has been validated. The results of the t-test showed a significant difference between the social skills of students who participated in sports activities and those who did not. Sports activities have been proven to increase student empathy, communication, cooperation, and a sense of responsibility. This study recommends schools to further develop sports extracurricular activities as a means of character education.